Sustainable Cotton Production in the Era of Climate Change: Challenges and Adaptive Measures - Khalid, Muhammad Nouman; Shakeel, Amir; Razzaq, Humera; Amjad, Ifrah; Amjad, Noreen (Journal of Agriculture and Biology, 2025)
Climate change is impacting agriculture, particularly cropping systems, in Pakistan due to rising temperatures and changing precipitation patterns. The cultivation of cotton (Gossypium spp.), a globally significant fiber crop, is becoming increasingly vulnerable to the adverse impacts of climate change. Cotton crops face various stresses due to climate change, including extreme temperature stress, drought stress, and salinity stress. Elevated temperatures during the reproductive phase of cotton adversely affect its growth and productivity by disrupting critical physiological processes, including germination, root development, and fruit formation. Similarly, drought stress remains a major limiting factor, particularly in arid and semi-arid regions where cotton is predominantly cultivated, resulting in suppressed plant growth and significant yield losses. Plants employ their mechanisms to adapt to drought conditions, but excessive moisture can also negatively impact growth and yield. Excessive salts in the soil profile and irrigation water trigger salinity stress, which adversely impacts cotton’s vegetative and reproductive growth, with young seedlings being especially sensitive. Air pollution stress, particularly ozone, can damage cotton plants, affecting yield and photosynthetic efficiency. Sustainable management practices, including mulching, cover cropping, and improved irrigation, play a pivotal role in minimizing stress-induced losses in cotton. Simultaneously, breeding for enhanced heat and drought tolerance is imperative for cultivar development. The chapter underlines the crucial role of water management, timely irrigation scheduling, and the strategic use of plant growth regulators (PGRs) in optimizing cotton productivity. Furthermore, the application of Decision Support Systems (DSS) and ICT tools supports efficient resource utilization and improves cotton growers' capacity to adapt to climatic challenges. Climate-smart agriculture (CSA) practices, aimed at boosting productivity, enhancing adaptability to climatic stresses, and curbing greenhouse gas emissions, are crucial for the sustainability of cotton farming. Climate-smart cotton practices and technologies can enhance production, improve farmers' livelihoods, and mitigate the adverse impacts of climate change on cotton cultivation. Adopting a climate-smart cotton production system is crucial for ensuring the sustainability of cotton cultivation in the face of the climate change challenges of this era.
Keywords: Climate change; Agriculture; Cotton; Drought; Salinity; Heat stress; Climate-smart agriculture